ASSESSMENT OF PATIENTS SATISFACTION ATTENDING OUTPATIENT DEPARTMENTS OF TEACHING HOSPITALS OF PESHAWAR - Khan, Liza; Hidayat, Hamna; Hussain, Irum; Khan, Javeria; Ali, Huma; Sethi, Mifrah Rauf; Irfan, Muhammad (Journal of Ayub Medical College Abbottabad, 2023)
Background: The doctor-patient relationship is a central feature of the healthcare system. The recent developments in the delivery of health care have tended to focus on patient satisfaction. Therefore, this study was planned to find out the satisfaction of patients attending the outpatient department of teaching hospitals in Peshawar. Methods: A cross-sectional study on Patients Satisfaction was conducted in outpatient departments of five different private and public teaching hospitals in Peshawar, Pakistan from March 2019 to March 2020. The questionnaire was translated into Pashto. All the patients consenting to participate were asked questions from Patient Satisfaction Questionnaire-18 (PSQ-18) by the principal investigator. The data was analyzed using SPSS Version 25. Results: The mean age of the sample (n=1025) was 37.58±15.60 years. There were 725 (70.1%) females and the majority were attending public sector hospitals (n=596, 58.1%). More than half of the sample (n=589, 57.5%) reported higher than mean scores on the Patient Satisfaction Questionnaire (PSQ). The insignificant gender difference was observed in terms of PSQ, whereas patients of public sector hospitals were more satisfied than patients of private sector hospitals (p=0.000). The inter-scale correlation using Pearson Coefficient between patient satisfaction and its subtypes showed a significant moderate positive correlation with a p-value of p=0.000. Conclusion: More than half of the patients showed satisfaction with the healthcare services. Patients attending public sector hospitals were more satisfied than the patients attending private sector hospitals.